1994
DOI: 10.1172/jci117165
|View full text |Cite
|
Sign up to set email alerts
|

Direct quantification of apparent binding indices from quinidine-induced in vivo conduction delay in canine myocardium.

Abstract: To characterize quantitatively the quinidine (QUIN)-induced conduction delay (CD) in vivo, canine ventricular activation times were examined with an epicardial mapping technique. A high-resolution index of normalized (N) QUIN CD, derived from all 56 recording sites, was used to quantify QUIN effect. Repetitive stimulation elicited monoexponential increases in CD(N), the rates of which were a linear function of interpulse recovery interval, t,. Steady-state CD(N) was also linearly related to an exponential func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…We previously reported a method for detecting local activation using a multiple unipolar lead system, [24][25][26][27] which allowed us to evaluate the degree of conduction delay quantitatively, from body 24,26 or cardiac surface electrodes. 28 The constructed activation sequence clearly detected the abnormality of local activation in myocardial ischemia, 24 infarction 25,27 or ventricular hypertrophy, 26 which indicated that the local conduction delay could predict the severity of exercise-induced myocardial ischemia, 24 the site of tiny myocardial infarction, 25 or the severity of hypertrophy. 26 However, to obtain this information, a complicated system is required.…”
Section: Clinical Implication: Relation To Clinical Observationmentioning
confidence: 93%
“…We previously reported a method for detecting local activation using a multiple unipolar lead system, [24][25][26][27] which allowed us to evaluate the degree of conduction delay quantitatively, from body 24,26 or cardiac surface electrodes. 28 The constructed activation sequence clearly detected the abnormality of local activation in myocardial ischemia, 24 infarction 25,27 or ventricular hypertrophy, 26 which indicated that the local conduction delay could predict the severity of exercise-induced myocardial ischemia, 24 the site of tiny myocardial infarction, 25 or the severity of hypertrophy. 26 However, to obtain this information, a complicated system is required.…”
Section: Clinical Implication: Relation To Clinical Observationmentioning
confidence: 93%